Sindaci e professionismo politico Uno studio di caso sui primi cittadini toscani - Corica, Graziana (Premio Ricerca «Città di Firenze», 2014)
The fil rouge of the work concerns the transformations of political professionalism, investigated through a particular category of politicians: the mayors of three municipalities in the provincial capitals of Tuscany, elected between 1994 and 2009. The reconstruction of the debate on the phenomenon, the legislative requirements and the regional political geography are the theoretical pillars on which the dual purpose of the research is based: first, to analyse the profile of the mayors in a diachronic perspective, and second, to interpret the different levels of political professionalism. The first perspective allows to illustrate the generational differences between the mayors after the introduction of the law 83/931. The second perspective focuses on the characteristics of the actors - defined on the basis of four dimensions of a continuum - and on the professionalisation of politics.